Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review: 46

Answer

$-\sqrt[3] {2x}$

Work Step by Step

$-3\sqrt[3] {2x}+\sqrt[3] {16x}$ =$-3\sqrt[3] {2x}+\sqrt[3] {8\times2x}$ =$-3\sqrt[3] {2x}+(\sqrt[3] {8}\times\sqrt[3] {2x})$ =$-3\sqrt[3] {2x}+(2\times\sqrt[3] {2x})$ =$-3\sqrt[3] {2x}+2\sqrt[3] {2x}$ =$-\sqrt[3] {2x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.